The Burden of Malnutrition and Fatal COVID-19: A Global Burden of Disease Analysis - Mertens, Elly; Peñalvo, José L. (Frontiers in Nutrition, 2021)
Background Although reasonable to assume, it is not yet clear whether malnourished countries are at higher risk for severe or fatal COVID-19. This study aims to identify the countries where prevalent malnutrition may be a driving factor for fatal disease after SARS-CoV-2 infection. Methods Using estimates from the Global Burden of Disease 2019, country-level burden of malnutrition was quantified using four indicators: death rates for child growth failure (underweight, stunting and/or wasting), and years lived with disability (YLD) attributed to iron and vitamin A deficiencies, and high body mass index (BMI). Global mortality descriptors of the ongoing COVID-19 pandemic were extracted from the European Centre for Disease Prevention and Control, and case fatality ratios (CFR) were calculated introducing a lag time of 10 weeks after the first death of a confirmed case. Bivariate analyses for 172 countries were carried out for malnutrition indicators and fatal COVID-19. Correlations between burden indicators were characterized by Spearman’s rank correlation coefficients () and visually by scatterplots. Restricted cubic splines and underlying negative binomial regressions adjusted for countries’ age-structure, prevalent chronic comorbidities related to COVID-19, population density and income group were used to explore non-linear relationships. Results Stratified by The World Bank income group, a moderate positive association between YLD rates for iron deficiency and CFR for COVID-19 were observed for low-income countries (=0.60, p-value=0.027), while no clear indications for the association with child growth failure, vitamin A deficiency or high BMI were found (<0.30). Countries ranking high on at least three malnutrition indicators and presenting also an elevated CFR for COVID-19 are sub-Saharan African countries namely Angola, Burkina Faso, Chad, Liberia, Mali, Niger, Sudan, and Tanzania, as well as Yemen and Guyana. Conclusions Population-level malnutrition appears to be related to increased rates of fatal COVID-19 in areas with an elevated burden of undernutrition, such as countries in the Sahel strip. COVID-19 response plans in malnourished countries, vulnerable to fatal COVID-19, should incorporate food security, nutrition, and social protection, as a priority component in order to reduce COVID-19 fatality.